Analysis of Factors Affecting Labor Productivity in the Processing Department of Cocoa ( Theobroma cacao L.) at PTPN XII Banjarsari Gardens, Jember, East Java - Julias, Prihastina Inung; Dhamayanthi, Wenny; Mahanani, Retno Sari (Politeknik Negeri Jember, 2023)
This research aims to determine 1) the influence of age, incentives, length of service, job satisfaction, stress, work discipline, and family responsibilities simultaneously on labor productivity 2) the influence of age, incentives, length of service, job satisfaction, stress, work discipline, and partial family responsibilities on labor productivity 3) which has the most dominant influence on labor productivity. The method used in this research is a survey method using a questionnaire as a data collection tool. The research sample consisted of 30 workers in the cocoa processing department at the Banjarsari plantation as respondents. The analysis method uses multiple linear regression analysis with simultaneous analysis techniques or F tests and partial tests or t tests. Based on the results of the F test, the variables age, incentives, length of service, job satisfaction, stress, work discipline and family responsibilities together do not have a significant effect on labor productivity. For the t test results, only the work discipline variable has a significant effect on labor productivity, while age, incentives, length of service, job satisfaction, stress and family responsibilities have no effect on labor productivity.